2003
DOI: 10.1213/01.ane.0000048826.67870.85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Alpha-Stat and pH-Stat Cardiopulmonary Bypass in Relation to Jugular Venous Oxygen Saturation and Cerebral Glucose-Oxygen Utilization

Abstract: A prospective, randomized study in 52 patients during cardiopulmonary bypass revealed that pH-stat increased jugular venous oxygen saturation and decreased arteriovenous oxygen-glucose differences. There was no difference in the incidence of jugular venous desaturation. These findings suggest an increased cerebral blood flow with no protection against jugular venous desaturation during pH-stat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…19 -21 However, CBF is dependent upon arterial blood pressure during pH-stat management. 18,20,22 It has been suggested that partial loss of cerebral autoregulation with pH-stat management may result in a cerebral "steal" phenomenon in patients with cerebrovascular disease and that increased CBF during CPB may result in an increased embolic load, thus potentially increasing the risk of cerebral injury. 18,[22][23][24][25] Traditional thinking holds that ␣-stat management better preserves cerebral flow-metabolism coupling and autoregulation of the cerebral vasculature 18 and that, during hypothermia, decreased cerebral metabolic demand and unchanged CBF cause SjvO 2 to increase, indicating "luxury perfusion."…”
Section: Discussionmentioning
confidence: 99%
“…19 -21 However, CBF is dependent upon arterial blood pressure during pH-stat management. 18,20,22 It has been suggested that partial loss of cerebral autoregulation with pH-stat management may result in a cerebral "steal" phenomenon in patients with cerebrovascular disease and that increased CBF during CPB may result in an increased embolic load, thus potentially increasing the risk of cerebral injury. 18,[22][23][24][25] Traditional thinking holds that ␣-stat management better preserves cerebral flow-metabolism coupling and autoregulation of the cerebral vasculature 18 and that, during hypothermia, decreased cerebral metabolic demand and unchanged CBF cause SjvO 2 to increase, indicating "luxury perfusion."…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kiziltan et al. (20) found significantly higher jugular venous oxygen saturations after 30 min of CPB at 27°C in patients managed according to the pH‐stat strategy compared with the alpha‐stat strategy (86.2% vs. 70.6%, respectively). Nevertheless, the incidence of desaturation during warming did not significantly differ between the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…59 Subsequently, cerebral autoregulation disappears and the risk of embolic events increases. 11,60,61 During rewarming period, and after CPB with moderate hypothermia, the alpha stat strategy is preferred to preserve an adequate cerebral oxygen supply demand balance and reduce acidosis.…”
Section: Cerebral Hypoperfusionmentioning
confidence: 99%